6(n+1)+3=45

Simple and best practice solution for 6(n+1)+3=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(n+1)+3=45 equation:


Simplifying
6(n + 1) + 3 = 45

Reorder the terms:
6(1 + n) + 3 = 45
(1 * 6 + n * 6) + 3 = 45
(6 + 6n) + 3 = 45

Reorder the terms:
6 + 3 + 6n = 45

Combine like terms: 6 + 3 = 9
9 + 6n = 45

Solving
9 + 6n = 45

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 6n = 45 + -9

Combine like terms: 9 + -9 = 0
0 + 6n = 45 + -9
6n = 45 + -9

Combine like terms: 45 + -9 = 36
6n = 36

Divide each side by '6'.
n = 6

Simplifying
n = 6

See similar equations:

| 0=9x^4-48x^2+64 | | 2x+4-x=17 | | 6x-2=20whatisx | | 317+x=360 | | 2[n+26]=264 | | (5+3d)+(8+2n)= | | 1/3x2=4 | | 12v=36+3v | | 5x-5/5=-6 | | 2(v-4)-6v=28 | | 4x-x-6=-14 | | x/3-1.5=4 | | 18=x+13+x+9 | | y=-2(3)-4 | | y+0.4x=3.60 | | -26.5=2d+6d | | (X-7)(x+6)(x-10)=0 | | t/3-2=7 | | 7x+8x-5=3(5x+7) | | -4(2t+2)=-16 | | 5+2.667x=24.5 | | y=-2(-3)-4 | | 4f-16=-12 | | 15+7y=22 | | -112=8y | | y=-2(-6)-4 | | 5x-5(-6-2x)=-20 | | X+17=2x+17+6 | | 13.5/45 | | [2x-9]=-14 | | 14/17=q/15 | | 25.5=-7.5+5(c-6) |

Equations solver categories